Clinical ethical conflicts of nurses and physicians - Gaudine, Alice (Nursing ethics, 2011)
Much of the literature on clinical ethical conflict has been specific to a specialty area or a particular patient group, as well as to a single profession. This study identifies themes of hospital nurses’ and physicians’ clinical ethical conflicts that cut across the spectrum of clinical specialty areas, and compares the themes identified by nurses with those identified by physicians. We interviewed 34 clinical nurses, 10 nurse managers and 31 physicians working at four different Canadian hospitals as part of a larger study on clinical ethics committees and nurses’ and physicians’ use of these committees. We describe nine themes of clinical ethical conflict that were common to both hospital nurses and physicians, and three themes that were specific to physicians. Following this, we suggest reasons for differences in nurses’ and physicians’ ethical conflicts and discuss implications for practice and research.